Acid, alkali and peroxide pretreatments increase the cellulose accessibility and glucose yield of banana pseudostem - Shimizu, Felipe Lange [UNESP]; Monteiro, Patrícia Queiroz; Ghiraldi, Pedro Henrique Ciconello [UNESP]; Melati, Ranieri Bueno [UNESP]; Pagnocca, Fernando Carlos [UNESP]; Souza, Wanderley de; Sant'Anna, Celso; Brienzo, Michel [UNESP] (Elsevier, 2018)
Lignocellulosic biomasses such as banana pseudostem are attractive cellulose sources for bioenergy production, and for the use in biorefinery processes. However, pretreatment of lignocellulosic material is required to remove hemicellulose and lignin, while increasing cellulose accessibility to enzymatic hydrolysis (i.e., decreasing biomass recalcitrance). The effect of different concentrations of acid (H2SO4), alkaline (NaOH) and peroxide (H2O2) pretreatments on the chemical composition, cellulose accessibility, and enzymatic digestibility of banana pseudostem were studied. The water insoluble solids (WIS) recovery was low (∼30%) for the severe pretreatment conditions applied, indicating high material solubilization. Acid pretreatment completely removed the hemicellulose content, whereas alkaline and peroxide pretreatments reduced its amount to 4.38 and 8.68%, respectively. In contrast, the lignin content increased (from 17.26 to 39.99%) after severe acid pretreatment, while alkaline and peroxide pretreatments reduced the lignin content to 7.65% and 7.17%, respectively. In line with hemicellulose and lignin removal, the cellulose content increased from 60.84 to 75.48 and 74.37%, respectively for alkaline and peroxide pretreatments, with no alteration for acid. Dye adsorption assays showed that alkaline and acid pretreatments resulted in high internal and external specific surface areas – indicative of high cellulose accessibility – when compared with peroxide pretreatments. Overall, alkaline and acid pretreatments resulted in the highest glucose yields from enzymatic hydrolysis of banana pseudostem, compared with peroxide pretreatment. In conclusion, concentrations of each pretreatment that led to the highest glucose yields was identified, confirming that the banana pseudostem is a great source of fermentable sugars, with high potential for biofuel production.
Keywords: Acid pretreatment; Alkaline pretreatment; Banana pseudostem; Glucose yield; Lignocellulosic biomass; Peroxide pretreatment; Recalcitrance